Manufacturing Strategy, Environmental Uncertainty and Performance: A Path Analytic Model - Swamidass, Paul M.; Newell, William T. (Management Science, 1987)
In recent years, researchers and practitioners are paying increasing attention to the phenomenon of manufacturing strategy. However, there exists no formal theory of manufacturing strategy to explain the phenomenon. There is a real need for empirical studies for the development of such a theory. This study takes a step in that direction by clarifying, organizing and integrating terms and concepts relevant to manufacturing strategy in the process of conducting an empirical investigation of key manufacturing strategy variables. The empirical section of this study based on data gathered from 35 manufacturers found that environmental uncertainty influenced manufacturing strategy variables such as Manufacturing Flexibility, and the Role of Manufacturing Managers in Strategic Decision Making. The manufacturing strategy variables, in turn, influenced business performance.